Contribution to the validation of Italian version of Fear-Avoidance Beliefs Questionnaire - Pruneti, Carlo; Sgromo, Domenico; Bicchieri, Lorenza; Fontana, Federico; Franceschini, Marco; Ferraro, Francesco; Cosentino, Chiara (Acta Biomedica Atenei Parmensis, 2014)
Background aim: propose further evidence for reliability and validity of Italian translation and adaptation of Fear Avoidance Beliefs Questionnaire, (FABQ) originally built-up by Waddel et al. (1993) Methods: 250 participants, inpatient and outpatient, suffering from acute or chronic back-pain have been consecutively recruited from various Italian physiotherapy and functional rehabilitation centres. All participants were administered FABQ and QUALEFFO, to evaluate if avoiding behaviors canprovoke disability independently from experimented pain. Results: Varimax rotation, point out a 4 factor structure: “Prognosis”, “Work as cause”, “Damage Expectancy”, “Physical activity as cause”. Statistical analysis underlined a good internal consistency. A good criterion validity resulted from correlation between FABQ scoring and QUALEFFO. The sample was splitted in “avoiders” (A) and “confronters” (C). Group A had no significant correlation between FABQ-W score and pain episode lasting, remission interval lasting, back-pain sick leave; no significant correlation emerged between beliefs and perceived pain. In group C a direct relation emerged between duration of sick leave, FABQ-W scores and FABQTOT scores, and an association between FABQ scores and reported pain. Conclusion: Pain-related fear and fear-avoidance beliefs are specific index which have to be considered in the first assessment phases, to prevent their effect on global functioning and on patients‘ quality of life. FABQ pointed out good reliability and validity propriety in Italian version. FABQ seems to be a brilliant instrument for multidisciplinary clinical practice in pain problem approach.